Platylomia kohimaensis n. sp.—a new cicada species (Hemiptera: Cicadidae) from the Naga Hills in the Eastern Himalayas - Hajong, Sudhanya Ray; Limatemjen (Zootaxa, 2021)
A new cicada species, Platylomia kohimaensis n. sp., belonging to the Platylomia radha group is described from the Naga Hills in the eastern Himalayas. It is a dusk singing, large-sized cicada that calls for a short window during the evening twilight hours. Timbalisation is in the form of a continuous and regular cackling. Photographs of adult male and female along with genitalia illustration and distribution map are provided. A sonogram along with Acoustic Identification Card is also provided.